2021
DOI: 10.3390/ma14061325
|View full text |Cite
|
Sign up to set email alerts
|

Self-Fluxing Mechanism in Geopolymerization for Low-Sintering Temperature of Ceramic

Abstract: Kaolin, theoretically known as having low reactivity during geopolymerization, was used as a source of aluminosilicate materials in this study. Due to this concern, it is challenging to directly produce kaolin geopolymers without pre-treatment. The addition of ground granulated blast furnace slag (GGBS) accelerated the geopolymerization process. Kaolin–GGBS geopolymer ceramic was prepared at a low sintering temperature due to the reaction of the chemical composition during the initial stage of geopolymerizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The quantitative analysis of coal-gangue-based geopolymer foams did not detect the kaolinite phase, which confirmed that during treatment the inner hydroxyl structure of kaolinite was reduced, and as a result, an amorphous substance material was formed [75]. Qualitative analysis of geopolymer (Table 6) showed new phases, which were albite and C-S-H, proving the reaction between raw materials and alkaline activator during geopolymerisation [76]. Similarly, results also revealed the mullite phase in all foams, whereas it was identified only in metakaolin from among raw materials.…”
Section: Geopolymersmentioning
confidence: 77%
“…The quantitative analysis of coal-gangue-based geopolymer foams did not detect the kaolinite phase, which confirmed that during treatment the inner hydroxyl structure of kaolinite was reduced, and as a result, an amorphous substance material was formed [75]. Qualitative analysis of geopolymer (Table 6) showed new phases, which were albite and C-S-H, proving the reaction between raw materials and alkaline activator during geopolymerisation [76]. Similarly, results also revealed the mullite phase in all foams, whereas it was identified only in metakaolin from among raw materials.…”
Section: Geopolymersmentioning
confidence: 77%
“…Different researchers have studied the DSC analysis of geopolymer concrete [103][104][105][106][107]. Jamil, N. H. et al [107] showed the geopolymer's range of thermograms (exothermal up) (Figure 24), where the geopolymer demonstrates some peaks in the matrix.…”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 99%
“…Different researchers have studied the DSC analysis of geopolymer concrete [103][104][105][106][107]. Jamil, N. H. et al [107] showed the geopolymer's range of thermograms (exothermal up) (Figure 24), where the geopolymer demonstrates some peaks in the matrix. Figure 25 depicts the differential scanning calorimetry (DSC) thermograms of geopolymer paste after 28 days, which are similar to the results reported in previous works [101].…”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 99%